Contextual Interpretation (Study of Epistemology, History, Variety of Books and Examples of Interpretation) - Kerwanto, K; Hasani, Muhammad Aulal Fikri Al; Hamdani, Muhammad Miftah (QiST: Journal of Quran and Tafseer Studies, 2024)
In the last few decades, interpretation with a contextual approach has begun to occupy a central position in the paradigm of interpreting the Qur'an. This is because the classical method of interpreting the Qur'an which is static and more textual is considered no longer compatible in responding to the reality of the era which is developing very complexly. This paper utilizes the library research method to examine the epistemological reasoning of contextual interpretation. The results of this study found that contextual interpretation is a form of approach in interpreting the Qur'an which starts from the argument that every text has a context that binds the meaning behind it. Thus, the meaning of a text of revelation (God's message) will only be found if an interpreter has a deep understanding of its context, then translated and elaborated based on the reality faced. In a different expression, contextual interpretation cannot be separated from the understanding of three horizons, namely between text, context, and contextualization.